Dark spaces : wildfire - Snyder, Scott; Snyder, Scott; Sherman, Hayden (IDW Publishing, 2023)
"Six weeks into the slow burn of the historic Arroyo Fire, a crew of women from an inmate firefighting program are risking everything on the frontlines when their newest recruit--a white-collar convict with a deep network of shady dealers--discovers they're mere miles from her crooked former associate's abandoned mansion. When she proposes a plan to abandon their duties and hunt for riches under cover of smoke and ash, the team must decide if they're ready to jeopardize their one sure path back to normalcy for a shot at a score that would truly change their lives...but is this a flicker of fortune, or a deadly trap?"--Back cover.